Influenza - Batura-Gabryel, Halina; Brajer, Beata (Przewodnik Lekarza/Guide for GPs, 2007)
Influenza is caused by a virus that attacks mainly the upper respiratory tract, and rarely also the lungs. Influenza rapidly spreads around the world in seasonal epidemics and imposes a considerable economic burden in the form of hospital and other health care costs and lost productivity. In annual influenza epidemics 5-15% of the population are affected with upper respiratory tract infections. In the very young, the elderly and people suffering from medical conditions such as lung diseases, diabetes, cancer, kidney or heart problems, influenza poses a serious risk. In these people, the infection may lead to severe complications of underlying diseases, pneumonia and death. Vaccination is the principal measure for preventing influenza and reducing the impact of epidemics. This paper presents the epidemiology, aetiology, risk groups, symptoms, contemporary methods of treatment and the importance of vaccination against influenza.